IMPROVING STUDENT’S SPEAKING ABILITY THROUGH MOBILE SOCIAL NETWORKING (Case Study : First Year Students of Stikes Yarsi Mataram - Danul Aristiawan (Journal of English Language Teaching and Literature (JELTL), 2022)
The aimed of this research was to find out whether the implanting of mobile social networking can be able to improve the student’s ability in speaking term of accuracy and fluency at first year students’ of Sikes Yarsi Mataram. This research was conducted through pre-experimental method. The population of this research consisted of one class of first year students’ of Sikes Yarsi Mataram which consisted of 31 students at Sikes Yarsi Mataram academic year 2020/2021. In collecting data, the researcher gave a speaking test, the speaking test help into two steps, there were pre-test and post-test, while to analyzed data , the researcher used (t)test. The findings of this research showed that the mean score in pre-test in term of pronunciation was (3,06) and post-test was (5,65). The mean score in pretest in term smoothness was ( 3,39) and post-test was (5,74). And the total result of pronunciation and smoothness or X1 was (3,22) and the post-test or X2 was (5,7). So, this is showed students got improvement in their speaking after being taught through mobile social networking, the students ability in speaking English became better than before